Mediating Role of Self-Efficacy on the Influence of Owner-Pet Relationship and Social Support on Pet-Owner Wellness - Macasa, Princess Marian; Orbon-Grijalvo, Myrtle (12th International Scholars Conference 2025, 2026)
Most people have deemed the importance of prioritizing one’s well-being, particularly during the COVID-19 pandemic. The purpose of this study is to determine the mediating role of self-efficacy on the influences between owner-pet relationship and social support on pet-owner wellness. The survey was participated by Filipino pet owners aged 18 to 65 who had owned a pet cat or dog for at least six months. They were recruited using purposive and snowball sampling methods. The participants completed an online survey through Google forms; and data were analyzed with Jamovi and R Core Team. The result shows very good relationship of owner-pet relationship, high social support from family, friends, and significant others. Self-efficacy and pet-owner wellness are also high. The path from the variables, social support and owner-pet relationship to pet-owner wellness is significantly correlated (p = <.001). Self-efficacy partially mediated the influences between owner-pet relationship and pet-owner wellness, and between social support and pet-owner wellness.